Gender, Violence, and Transformation in Alice Walker's 'The Color Purple' - Kirk-Duggan, Cheryl A. (Curing violence, 1994)
Abstract:Alice Walker's classic novel, The Color Purple, celebrantes the transformation of Black women and critiques the violent abuse that characterizes the human condition. The novel focuses on the relationship between Celie and God as it dramtically unfolds within various communities, but most especially, the Black female community. In so far as the text reflects persecution, The Color Purple makes an intriguing case study for analyzing René Girard's theories about scapegoats and violence. The context for Celie's personal journey to freedom and wholeness is a primal myth of violence and scapegoating: the patriarchal myth of male domination over women. But unlike Girard, who dismisses first person narrative accounts of victimage, Walker demands that the reader enter the world of the text as the one victimized. This chapter focuses on Celie as "suffering servant" and scapegoat, as set overagainst violence and the socializing control of domination. Feminist and rhetorical hermeneutics provide the resources for analyzing the myths and rituals that perpetuate violence, and for abserving Walker's model for nonviolent transformation. Nonviolent transformation replaces the Girardian mimetic rivalry with agape, actualized as Theophus Smith's concept of mimetic intimacy (see chapter 11). Mimetic intimacy with God frames Celie's existence. Such intimacy grounds her experience of theodicy, and forges her life within a theology of creation where sexuality celebrates the communion of humanity. Rather than a Girardian cure by means of the sacrificial death of a scapegoat, Walker cures violence through self-actualization nurtured by agape. The royal color purple symbolizes transformation: new life for victims and victimizers. (Source: Cheryl A. Kirk-Duggan)